Hubungan Atribut Produk terhadap Keputusan Pembelian Beras Lokal Unggulan Kabupaten Mempawah - Wardani, Sri; Dolorosa, Eva; Kurniati, Dewi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Mempawah Regency possesses Superior Local Rice that serves as a prima donna. However, the threat of competition from imported rice competitors poses a challenge to the development of superior local rice. This research aims to analyze the relationship of product attributes to the purchasing decisions for Mempawah Regency's superior local rice. A descriptive qualitative approach is employed to explain the research findings, with 200 respondents analyzed using Spearman rank correlation. The research results indicate that all attribute variables of Mempawah Regency's superior rice are significantly correlated with purchasing decisions. The variables of Taste, Appeal, and Cleanliness attributes of the superior local rice exhibit a "Strong" category relationship strength. The attributes of Aroma, Color, Packaging Safety, and Packaging Attractiveness have a "Medium" category relationship strength, while the Texture attribute has a "Weak" category relationship strength. These findings affirm that the purchasing decision for Bestari rice is the result of a complex combination between core product quality and product appearance factors.